The Effect of Adding Recycled Concrete Aggregates on Asphalt Mixture Modified with Tire Rubber Crumbs - An Experimental and Numerical Study - Kusie Masri,; Marwan Assi,; Fatima Alsaleh, (International Journal of Sustainable Construction Engineering and Technology, 2024)
The accumulation of huge amounts of rubble and the worn-out tires that resulted from the severe damage to Syrian facilities because of the current war in Syria poses a serious environmental problem. In this research, therefore, asphalt mixtures containing recycled concrete aggregates and an asphalt binder modified with tire rubber crumbs were designed. It also determines the loading cycles until failure on fatigue and rutting of these mixtures by following numerical modeling and using the 3D-Move Analysis program.The results showed an increase in the optimal asphalt ratio, the proportion of air voids and flow with the increase in the proportion of recycled concrete aggregates in the asphalt mixture. Contrastingly, it showed a decrease in both volumetric density and stability with the increase in the proportion of these aggregates in the mixture. With modifying these mixtures with tire rubber crumbs, both of the percentage of air voids and stability increase, while the volumetric density and flow decrease. The results also showed an increase in the fatigue strength of the asphalt mixture with an increase in the proportion of recycled concrete aggregates, while the rutting resistance increased when the mixture was modified with tire rubber crumbs.